(3GdJShjb GdeUQaj (B:s (3eONd eJcGed ddHfhc dEeJdGc efXheI GdeRGjG GdJfGaSjI aj YGde eG HYO GdLGJ (B/s - (3GdNVjQj, eMSf CMeOs ((3GdbGgQI(B: s (3GjJQGc ddfTQ hGdJhRjY(B, s, 1999)
(3OhQ GdJShjb aj EOGQI GdfTGW GdeUQaj(B- (3OQGSI GdYejd hGdShb GdeUQaj(B- (3ENJjGQ ehbY hJhRjY THcI aQhY GdHfc(B- (3JQhjL GdNOeGJ GdeUQajI(B- (3JWhjQ eRjL GdNOeGJ GdeUQajI(B- (3GSJQGJjLjGJ GdJShjb GdeUQaj(B- (3GdQbGHI Ydi fTGW GdJShjb GdeUQaj(B-(3GdeaGhVGJ GdJShjbjIs
Keywords: (3GdHfhcs; (3GdJShjbs; (3GdJShjb GdeUQajs